THE USE OF GENERIC DRUGS IN PHARMACY IN THE MUNICIPALITY OF YOGYAKARTA DURING MONETARY CRISIS (OBSERVATION ON MARCH 1997 - MARCH 1998) - Andari, Irin Dwi; Wahyono, Djoko (INDONESIAN JOURNAL OF PHARMACY, 2001)
Monetary crisis that strike Indonesia had also impacts on health services either private or public services, including pharmaceutical industries. The industries had difficulty to find raw materials for production which in turn resulting in scarce and the rise of drug price. The situation could urged the patients to shift of using the patented medicines into generic ones which are relatively cheaper. The present study has therefore aimed to observe the usage of generic products before (March 1997 - August 1997) and during (September 1997 - March 1998) the monetary crisis periods in five pharmacies of Yogyakarta Municipality. The data were taken from the stocks units and from doctorâs prescriptions, which were then analyzed by ANAVA (p=0,5). Other data were also collected and analyzed descriptively from questionnaires requested to the a hundred of pharmacyâs visitors at the same periods as above.The results have shown that the number of generic product usage was not different between the two periods, except amoxycillin 500 mg, antalgin, dextrometorphan, captopril 25 mg, and glibenclamide tablets. The respondents have revealed that they have information on generic products (91%) from mostly mass media (44%). As many as 39 % of them assume that the generic products are cheaper than of patented products and it has the same effect.Key words : monetary crisis, generic product, pharmacies